Differences in the prognostic value of tumor size on hepatocellular cancer‐specific survival stratified by gender in a SEER population‐based study. Issue 7 (1st August 2019) - Zhang, Wenjie; Jin, Kangpeng; Wang, Fei; Zhangyuan, Guangyan; Yu, Weiwei; Liu, Yang; Zhang, Haitian; Zhang, Ping; Sun, Beicheng
Abstract : Background and objective: Tumor size is an important prognostic factor in cancers. This study aims at investigating the interaction between gender status and tumor size to evaluate cancer‐specific survival (CSS) in hepatocellular carcinoma (HCC). Methods: In this study, we searched Surveillance, Epidemiology, and End Results (SEER) population‐based data and identified 38, 368 patients diagnosed with HCC between 1988 and 2012. Patients diagnosed between 1998 and 2007 were distributed into a training set ( n  = 19279), and the rest were assigned as a SEER validation set ( n  = 19089). Definition of cut‐off value of tumor size stratified by gender was determined by the "X‐Tile" program. The five‐year CSS data were found. Long‐term survival outcomes and risk factors were analyzed by the Kaplan–Meier methods and the multivariable Cox regression models. Results: There were significant differences among these different tumor size subgroups with regards to five‐year CSS ( p  < 0.001). When applying cutoff points of 38 mm and 75 mm tumor size in men, and 38 mm and 55 mm in women, the most significant difference was observed by the X‐Tile program, respectively ( p  < 0.001). The five‐year CSS was 27.5% for women and 25.7% for men in the training set, and 33.9% for women and 31.1% for men in the validating set ( p  < 0.001). Further analysis showed that this significant difference existed in localized, regional, and distant‐stage patients. Conclusions: These results demonstrated that women with HCC appeared to exhibit better survival rates than men. The sex‐related discrepancies should be emphasized, particularly for HCC patients with 39 to 75 mm tumors.